Trait approach motivation moderates the aftereffects of self-control - Crowell, Adrienne; Kelley, Nicholas J.; Schmeichel, Brandon J. (Frontiers in Psychology, 2014)
Numerous experiments have found that exercising self-control reduces success on subsequent, seemingly unrelated self-control tasks. Such evidence lends support to a strength model that posits a limited and depletable resource underlying all manner of self-control. Recent theory and evidence suggest that exercising self-control may also increase approach-motivated impulse strength. The two studies reported here tested two implications of this increased approach motivation hypothesis. First, aftereffects of self-control should be evident even in responses that require little or no self-control. Second, participants higher in trait approach motivation should be particularly susceptible to such aftereffects. In support, exercising self-control led to increased optimism (Study 1) and broadened attention (Study 2), but only among individuals higher in trait approach motivation. These findings suggest that approach motivation is an important key to understanding the aftereffects of exercising self-control.